Sphingosine kinase 1 mediates sexual dimorphism in fibrosis in a mouse model of NASH - David Montefusco; Maryam Jamil; Melissa A. Maczis; William Schroeder; Moshe Levi; Suman Ranjit; Jeremy Allegood; Dipankar Bandyopadhyay; Reuben Retnam; Sarah Spiegel; L. Ashley Cowart (Elsevier, 2022)
Objective: Men with non-alcoholic fatty liver disease (NAFLD) are more likely to progress to non-alcoholic steatohepatitis (NASH) and liver fibrosis than women. However, the underlying molecular mechanisms of this dimorphism is unclear. We have previously shown that mice with global deletion of SphK1, the enzyme that produces the bioactive sphingolipid metabolite sphingosine 1-phosphate (S1P), were protected from development of NASH. The aim of this study was to elucidate the role of hepatocyte-specific SphK1 in development of NASH and to compare its contribution to hepatosteatosis in male and female mice. Methods: We assessed mouse livers in early-stage fibrosis induced by high fat feeding, using single harmonic generation microscopy, LC-MS/MS analysis of hydroxyproline levels, and expression of fibrosis markers. We identified an antifibrotic intercellular signaling mechanism by culturing primary mouse hepatocytes alongside, and in co-culture with, LX2 hepatic stellate cells. Results: We generated hepatocyte-specific SphK1 knockout mice (SphK1-hKO). Unlike the global knockout, SphK1-hKO male mice were not protected from diet-induced steatosis, inflammation, or fibrogenesis. In contrast, female SphK1-hKO mice were protected from inflammation. Surprisingly, however, in these female mice, there was a ∼10-fold increase in the fibrosis markers Col1α1 and 2-3 fold induction of alpha smooth muscle actin and the pro-fibrotic chemokine CCL5. Because increased fibrosis in female SphK1-hKO mice occurred despite an attenuated inflammatory response, we investigated the crosstalk between hepatocytes and hepatic stellate cells, central players in fibrosis. We found that estrogen stimulated release of S1P from female hepatocytes preventing TGFβ-induced expression of Col1α1 in HSCs via S1PR3. Conclusions: The results revealed a novel pathway of estrogen-mediated cross-talk between hepatocytes and HSCs that may contribute to sex differences in NAFLD through an anti-fibrogenic function of the S1P/S1PR3 axis. This pathway is susceptible to pharmacologic manipulation, which may lead to novel therapeutic strategies.